The Effectiveness of the Problem-Based Learning Model in Contemporary Fiqh Learning on the Topic of Marriage Contracts at Madrasah Aliyah Negeri 1 Padang - Rina Windari Lubis; Khadijah; Widya Sari (Lembaga Publikasi Ilmiah Universitas Islam Bunga Bangsa Cirebon, 2026)
This study aims to analyze the effectiveness of the Problem Based Learning (PBL) model in teaching contemporary Fiqh, particularly the topic of contract marriage, at Madrasah Aliyah Negeri 1 Padang through a library research approach. PBL is viewed as a learning model that encourages students to think critically, independently, and analytically in understanding modern fiqh issues that are problematic and controversial in nature. The topic of contract marriage was selected because it constitutes an important part of contemporary fiqh studies, requiring an in-depth understanding of religious evidence, social context, and differences in opinion among classical and modern Islamic scholars. This research employs various literature sources, including books, academic journals, previous research findings, and curriculum documents relevant to Fiqh instruction in madrasahs. The results of the analysis indicate that PBL is effective in contemporary Fiqh learning, as it is able to integrate real-life problems as triggers for discussion, enhance higher-order thinking skills, and habituate students to engage with current issues in a scientific and analytical manner. In the context of contract marriage material, PBL assists students in understanding legal, social, and ethical aspects through processes of investigation, information gathering, and evidence-based argumentation. Furthermore, PBL aligns with the characteristics of the Merdeka Curriculum and the demands of 21st-century learning, which emphasize collaboration, problem-solving skills, and digital literacy. Therefore, based on the literature review, the PBL model can be considered relevant and effective in improving the quality of contemporary Fiqh learning at Madrasah Aliyah Negeri 1 Padang, particularly for topics that require critical reasoning such as contract marriage.